A Fábrica de papel da Lousã e o processo de industrialização em Portugal - Campos, Maria do Rosário Castiço de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Since the foundation in Lousã, in the early 18th century, until the middle of the 19th century, the paper factory has gone through different changes. Its installation has taken place during the reign of D. João V and the royal decision occurred because of a request made by an Italian manufacturer. The particular conditions found in the municipality of Lousã were extremely important in the process of deciding its location, as we will show in this study.